2021
DOI: 10.3389/fcvm.2021.757799
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Myoglobin for COVID-19-Related Adverse Outcomes: A Systematic Review and Meta-Analysis

Abstract: Objective: Cardiac injury is detected in numerous patients with coronavirus disease 2019 (COVID-19) and has been demonstrated to be closely related to poor outcomes. However, an optimal cardiac biomarker for predicting COVID-19 prognosis has not been identified.Methods: The PubMed, Web of Science, and Embase databases were searched for published articles between December 1, 2019 and September 8, 2021. Eligible studies that examined the anomalies of different cardiac biomarkers in patients with COVID-19 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
1
20
0
2
Order By: Relevance
“…For non-vaccinated groups, the present study showed that Myoglobin was significantly higher (P<0.0001) in individuals infected with CoV-19 virus and non-vaccinated more than patients that non-vaccinated and recovery from covid-19 as indicated in the Figure 5. The current results were compatible with the research of [49] that revealed the increased myoglobin was more prevalent in individuals with severe CoV-19 virus than in cardiac troponin I. Therefore, increased Mb may be used as a determinant of adverse COVID-19 outcomes.…”
Section: Estimation Of Serum Myoglobin Concentrationssupporting
confidence: 91%
“…For non-vaccinated groups, the present study showed that Myoglobin was significantly higher (P<0.0001) in individuals infected with CoV-19 virus and non-vaccinated more than patients that non-vaccinated and recovery from covid-19 as indicated in the Figure 5. The current results were compatible with the research of [49] that revealed the increased myoglobin was more prevalent in individuals with severe CoV-19 virus than in cardiac troponin I. Therefore, increased Mb may be used as a determinant of adverse COVID-19 outcomes.…”
Section: Estimation Of Serum Myoglobin Concentrationssupporting
confidence: 91%
“…Mortality & Severity ↑ (Kermali et al, 2020;Tian et al, 2020;Vakhshoori et al, 2020b;Toraih et al, 2020;Parohan et al, 2020;Shoar et al, 2020;Rathore et al, 2021;Alzahrani and Al-Rabia, 2021;Wibowo et al, 2021) TnT Li et al, 2020a;Parohan et al, 2020;Li et al, 2020c;Zheng et al, 2020;Ma et al, 2021;Zhu et al, 2021) NT Parohan et al, 2020;Li et al, 2020c;Shoar et al, 2020;Malik et al, 2021;Zhu et al, 2021) (Continued)…”
Section: Cardiac Troponinunclassified
“…The tissue injury marker, myoglobin, and D-dimer levels have been used to predict the severity of COVID-19 patients. These biomarkers possess significant predictive potential in evaluating disease outcomes in COVID-19 patients [9] , [10] . The robust correlations of dysregulated GFs with these biomarkers may help identify whether aberrant levels of GFs in COVID-19 are pathological or compensatory.…”
Section: Introductionmentioning
confidence: 99%